Analisis Efisiensi Pemasaran Nanas (Ananas Comosus. L) (Studi Kasus: Di Kelurahan Tuatunu Indah Kecamatan Gerunggang Kota Pangkalpinang) - Vanni Novita Sari Sihombing; Yulia Yulia; Iwan Setiawan (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Province of Bangka Belitung has considerable potential in the field of horticulture. One of the horticultural fields that is quite large is pineapple which has the potential in Tuatunu Indah Village. The amount of pineapple production is not accompanied by the price received by farmers and the large difference in the price received by farmers and the price paid by consumers. So with this research the researcher aims to describe the marketing channels and functions of pineapple in Tuatunu Indah Village and analyze the efficiency of pineapple marketing in Tuatunu Indah Village. The method used in this research is the case study method. %.Â Â  The sampling technique used in this research is the snowball sampling technique. The data analysis method used in this research is descriptive, qualitative and quantitative. The results showed that the marketing channel of pineapple in Tuatunu Indah Village, Gerunggang Subdistrict, Pangkalpinang City consisted of 4 marketing channels, namely channel I which consisted of farmers and end consumers. Marketing channel II is a channel consisting of farmers, retailers and end consumers. Marketing channel III is a channel consisting of farmers, middlemen, retailers and end consumers. Channel IV is a channel consisting of farmers, wholesalers, retailers and end consumers. The marketing functions carried out on each marketing channel of pineapple in Tuatunu Indah Village, Gerunggang Subdistrict, Pangkalpinang City are the functions of buying, selling, harvesting, transporting, sorting and grading, storage, risk, cost and market information. The marketing efficiency of pineapple in Tuatunu Indah Village, Gerunggang Subdistrict, Pangkalpinang City on channels I to IV has a marketing efficiency value of 15,28%, 14,89%, 24.69% and 52,86%. Based on the value of marketing efficiency from channels I to IV, it shows that channels I to III are efficient because the efficiency value is 50%, while for channel IV it is not efficient because it has a marketing efficiency value of 50%.